Sustainability of Batik Sekar Jati Star Jombang Business in Building Creative Economy in The New Normal Era - Ahmad Nur Ismail; Shufyani Azzahro; Khotim Fadhli; Arivatu Ni’mati Rahmatika (INCOME: Innovation of Economics and Management, 2021)
This research aims to find out productivity, marketing, increased competitiveness, and improvement of creating economic development in the new normal era in Batik Sekar Jati Star Jombang. This study uses a qualitative approach with qualitative descriptive research type. Data collection techniques in this study use observations, interviews, documentation. The results of the study showed that the speed in building economist creativity in the new normal era in batik Sekar jati star Jombang business is: first, productivity using output (output) and input (input) by predicting from the previous months. Second, marketing uses strategies that are only sold in the market, WhatsApp, and COD media. Third, increase competitiveness using good means of facilitating and allowing buyers to see the process of making them.